Integrasi Life Skill dalam Latihan Sepakbola Siswa SSB Usia 12 dan 13 Tahun - Muhamad Tafaqur (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
This study aimed to determine the effect of integrated and non-integrated life skills on improving the life skills of Football School students. The method used in this research was the experimental method. The design used in this study was the pre-test and post-test control group design. The samples of this study were 20 male students aged 12 and 13 years old (12.7+1.1). The sampling process used a purposive sampling technique. Students were divided into two groups, the experimental group of 10 students and the control group of 10 students. The instrument used was the Life Skills Scale for Sport questionnaire. The results showed that the integrated life skills in the football training program significantly affected the life skill improvement of Football School students aged 12 and 13 years. In comparison, the non-integrated life skills in football practice had no significant effect on the life skill improvement of Football School students aged 12 and 13. The results of this study could be a consideration for young football coaches when compiling a youth soccer training program.